Renal Replacement Lipomatosis with Coexistent Papillary Renal Cell Carcinoma, Renal Tubulopapillary Adenomatosis, and Xanthogranulomatous Pyelonephritis An Extremely Rare Association and Possible Pathogenetic Correlation - Prerna Arora; Seema Rao; Nita Khurana; Vinod Kumar Ramteke (Urology Journal, 2013)
No Abstract